Student engagement- a promissing solution to quality improvement of Vietnamese higher education - Nguyen, Thi Thu Trang; Do, Van Dung (Journal of Technical Education Science, 2018)
‘Student engagement’ defined as the time and the quality of effort students put into their learning and their involvement in educationally purposeful activities, is a prominent and ubiquitous topic in contemporary higher education scholarly literature and practices in the world. Because of its significant influences on students’ academic and personal development during university, student engagement is widely recognized as a powerful lever for higher education quality improvement. This theme, however, is quite new to the Vietnamese higher education system. Based on the synthesis and analysis of scholarly literature on student engagement and the Vietnamese higher education system, this paper presents the construct of ‘Student engagement’, indicates student disengagement-related problems Vietnamese higher education is facing, and explains how ‘Student engagement’ with its strong link with student learning and student success can offer Vietnamese universities a promising solution to these problems, thus to their quality improvement.